Analisis Kelayakan Pembangkit Listrik Tenaga Surya Rooftop 369,36 kWp Berbasis Leasing di Perusahaan Listrik XYZ - Abhirama, Ivan; Novasani, Raditya Jarwenda (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing demand for electrical energy has encouraged XYZ Electricity Company to optimize the use of renewable energy, one of which is through rooftop Solar Power Plants (PLTS). This study aims to analyze the contribution of rooftop PLTS with a capacity of 369.36 kWp to increasing PS efficiency. This study is a quantitative study that uses operational data from the generating unit's own consumption and PLTS energy production data as samples, which are analyzed through a comparison of conditions before and after the implementation of PLTS. The results show that rooftop PLTS is able to reduce energy needs from the main generating system, increase PS efficiency especially during the day, and provide economic benefits through reduced electricity costs. Therefore, optimization of rooftop PLTS is recommended as a strategy to increase energy efficiency and the operational sustainability of power plants.